2018
DOI: 10.1177/0300060518772227
|View full text |Cite
|
Sign up to set email alerts
|

Optimal neuromuscular blocking effects of remifentanil during tracheal intubation under general anesthesia

Abstract: ObjectiveThis study was performed to determine the effect of the remifentanil dose on the onset time of rocuronium with electromyography.MethodsThis retrospective comparative study included 75 patients undergoing general anesthesia for elective surgery. Patients received lidocaine (40 mg) and propofol (2 mg/kg) followed by rocuronium (0.6 mg/kg) with either saline infusion (Group S), remifentanil at 0.5 µg/kg/minute (Group R 0.5), or remifentanil at 1.0 µg/kg/minute (Group R 1.0). Neuromuscular block was monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…29 The emergence of other possible adjuncts with established adverse risk profiles, such as remifentanil, appear to have made little impact on reducing doses of NMBAs. 58 A strength of this prospectively registered systematic review is that it adhered to international recommendations for this type of article. We used the GRADE criteria to assess the overall quality of evidence (Supplementary material S10).…”
Section: Discussionmentioning
confidence: 99%
“…29 The emergence of other possible adjuncts with established adverse risk profiles, such as remifentanil, appear to have made little impact on reducing doses of NMBAs. 58 A strength of this prospectively registered systematic review is that it adhered to international recommendations for this type of article. We used the GRADE criteria to assess the overall quality of evidence (Supplementary material S10).…”
Section: Discussionmentioning
confidence: 99%
“…The significant negative correlation between the amount of fentanyl and lidocaine and the onset time of the NMB indicated that the higher the dose of fentanyl and lidocaine, the shorter the NMB onset. However, a previous study described that remifentanil, which is also an opioid mu-receptor agonist, increases the time required to reach TOF=0 in a dose-dependent way in human patients 26. In the present study, the use of fentanyl and lidocaine without a significant decrease in the fraction of expired isoflurane could have enhanced muscle relaxation indirectly and, therefore, decreased the NMB onset.…”
Section: Discussionmentioning
confidence: 46%
“…However, a previous study described that remifentanil, which is also an opioid mu-receptor agonist, increases the time required to reach TOF=0 in a dose-dependent way in human patients. 26 In the present study, the use of fentanyl and lidocaine without a significant decrease in the fraction of expired isoflurane could have enhanced muscle relaxation indirectly and, therefore, decreased the NMB onset. In addition, the fentanyl and lidocaine groups had a higher number of dogs administered boluses of crystalloid and colloid, suggesting that they had episodes of hypotension requiring intravascular volume expansion.…”
Section: Discussionmentioning
confidence: 51%